The myth of 9/11 - Formby, Zoë (2011)
Conceptualisations of modern literary history are premised upon a series of dynastic successions, whereby one is able to trace, albeit simplistically, the evolution of the novel through its realist, modernist and postmodernist manifestations. Considered in this linear manner, the emergence of altered cultural movements is ordinarily attributed to a crisis within the former mood; as society ruptures and alters, existing modes of representation prove inadequate to reflect, or else engage with, the emergent structure of feeling. As an event with far-reaching implications, many critics and cultural commentators have attributed the terrorist attacks of September 11, 2001 with the inception of an altered global mood. Moreover, in the days and weeks following 9/11, the publication of a number of articles penned by authors emphasised the extent to which the event had precipitated a profound crisis in representation. As an ever greater number of articles and studies emerged proclaiming the final death knell of postmodernism and the emergence of a more anxious global mood, so the myth of 9/11 quickly developed.